Known Knowns, Known Unknowns, and Unknown Unknowns: Coverage in MS Experiments. Issue 16 (6th August 2018) - Koziol, James A.; Li, Yan; Schnitzer, Jan E.
Abstract: A mathematical model from ecology, namely, the capture–recapture model with a closed population and time‐varying and heterogeneous individual probabilities of capture, is implemented to model the number of protein identifications across the various cycles of a mass spectroscopy experiment. Rcapture, a package available in the R computing environment, can easily provide estimates of the cardinality of the proteome from such experiments. Alternatively, model fitting can be undertaken in other software platforms, such as Matlab, that can accommodate general linear models. It has not escaped our notice that capture–recapture models can be more broadly applied to other settings, so as to estimate the number of missing observations in an experiment.